THERAPEUTIC EFFECTIVENESS OF BROMETRONID NEW UNDER QUAIL EIMERIOSIS - Dovhiy, Y. Y.; Rudik, O. V. (Scientific Progress & Innovations, 2020)
The paper presents the results of the scientific-production research, by which it has been established that mono-invasion is observed in quails. The invasion intensity made as follows: Е. tenella – 1.1±0.07 thousand oocysts, E. necatrix – 960±0.04 oocysts, E. acervulina – 1.3±.0.02 thousand oocysts per1 g of dung. Quails of the first experimental group were given Brometronid New preparation at a dose of 2 gr per 1 kg of compound poultry feed without immune-modulator for 5 days, and the second experimental group received eimeriostatic (Brometronid New) at a dose of 1g per 1 kg of compound poultry feed in combination with immune modulator – Chinese magnolia vine (Schinsandra chinensis) potion at a dose of 1cm³ per 1 liter of water during 5 days with drinking water. As a result of laboratory analysis of dung samples, on the 14th and 21st days the extense-effectiveness and intense-effectiveness made 100 %. The increase in morphological and biochemical blood in-dices was observed in the first experimental group. On the 7th day, the number of erythrocytes increased by 18.5 %, Р˂0.001, basophils – by 31.4 %, Р˂0.001, lymphocytes by 7.6 %, Р˂0.05, and on the 14th day, the number of pseudo-eusinophiles increased by – 7.8 %, Р˂0.05. Such indices as eosinophiles, leukocytes, mono-cytes on the 7th day tended to increase, and on the 14th day they decreased to minimum physiological indices. Blood biochemical analysis showed that on the 7th day, an increase of crude protein content by 30.9 %, Р˂0.001, calcium by 20.3 % Р˂0.001, cholesterol by 0.37 %, Р˂0.05, phosphorus by 49.9 %, Р˂0.01was reg-istered, and on the 14th day hemoglobin increased by 13.5 %, Р˂0.001, total bilirubin by 5.65 %, Р˂0.05, cre-atinine by 5.9 %, Р˂0.05, АlАТ by 40.5 %, Р˂0.01, АсАТ by 8.8 %, Р˂0.05, LF by 35.8 %, Р˂0.01, potassi-um by14.6 %, Р˂0.001, glucose by 17.2 %, Р˂0.001, uric acid by 38.2 %, Р˂0.01. The results, received from the second experimental group, testified that on the 7th and 14th days some positive changes in morphological and biochemical blood indices were observed as compared with the 1st day. In morphological indices on the 7th day, an increase in the number of erythrocytes by 17.6 %, Р˂0.001, leukocytes by 10.7 %, Р˂0.05, lympho-cytes by 16.3 %, Р˂0.001 was observed, and on the 14th day the number of erythrocytes increased by 32.7%, Р˂0.01 and pseudo-eosinophiles increased by 2.6 %, Р˂0.05. In biochemical indices of the second experi-mental group on the 7th day, as compared with the 1st day, the increase in total calcium by 20.7 %, Р˂0.001, cholesterol by 37.4 %, Р˂0.01, АсАТ by 2.3 %, Р˂0.05, LF by 45.7 %, Р˂0.01, phosphorus by15.6 %, Р˂0.001, potassium by 44.7 %, Р˂0.01, uric acid by 10.2 %, Р˂0.05 was registered, and on the 14th day the content of hemoglobin increased by 26.8 %, Р˂0.01, creatinine by 17.9 %, Р˂0.001, uric acid by – 53 %, Р˂0.01, total protein by 17.3 %, Р˂0.001. From the results, obtained in the second group of quails, an in-crease in hemoglobin content, as well as total calcium, cholesterol, creatinine, alkaline phosphatase, phospho-rus, potassium, total protein, uric acid was registered. We consider, these changes were caused by immune stimulating action of Chinese magnolia vine (Scisandra chinensis) potion. The decrease in biochemical indices of total bilirubin, glucose, AlAT as compared with healthy poultry was observed as well.